Inefficiency in Social Security Trust Funds Forecasts - Kajal Lahiri; Junyan Zhang; Yongchen Zhao (Center for Economic Studies and ifo Institute (CESifo), 2021)
We examine forecast accuracy and efficiency of the Social Security Administration's projections for cost rate, trust fund balance, trust fund ratio made during 1980-2020 with horizons up to 95 years. We find that the reported deterioration in the accuracy of the forecasts during 2010's has reversed. The level of informational inefficiency was pervasive during 1990-2009, although it shows signs of improvement after 2010.
Keywords: C53; E37; E66; H55; H68; 330; social security trust funds; long-range solvency forecasts; Nordhaus test; forecast efficiency; fixed-event forecast revisions